People Participation Development in Community Development at Wang Mun Sub-district, Wat Sing District, Chainat Province - Thongswang, Surawan; Kerdphon Prasopsak, Wasita; Subruangthong, Waraporn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2025)
This study aimed to: 1. examine the level of public participation, and 2. propose guidelines for enhancing public participation in community development in Wang Man Subdistrict, Wat Sing District, Chainat Province. The sample consisted of 328 residents of Wang Man Subdistrict, selected through stratified random sampling, along with a target group of 7 key informants. Data collection instruments included a 25-item questionnaire with a reliability coefficient of 0.768 and a semi-structured interview form. Data were analyzed using percentage, mean, standard deviation, and content analysis. The research findings revealed that: 1. the overall level of public participation in community development was at a moderate level. Ranking by mean scores, participation in receiving benefits was highest, followed by participation in operations, decision-making, and evaluation, respectively; and 2. guidelines for enhancing public participation in community development included: (i) creating communication channels through various media to encourage public involvement; (ii) providing opportunities and stimulating all community members to participate in every community activity; (iii) promoting understanding that benefits gained from activities are shared, initially starting with small groups to serve as examples; and (iv) building knowledge and understanding of evaluation processes to engage the public in monitoring and evaluating activities.